A Simultaneous Inversion Problem for the Variable-Order Time Fractional Differential Equation with Variable Coefficient. (13th January 2019) - Wang, Shengnan; Wang, Zhendong; Li, Gongsheng; Wang, Yingmei
Abstract : This paper deals with an inverse problem of simultaneously determining the space-dependent diffusion coefficient and the fractional order in the variable-order time fractional diffusion equation by the measurements at one interior point. Numerical solution to the forward problem is given by the finite difference scheme, and the homotopy regularization algorithm is applied to solve the inverse problem utilizing Legendre polynomials as the basis functions of the approximate space. The inversion solutions with noisy data which give good approximations to the exact solution demonstrate effectiveness of the inversion algorithm for the simultaneous inversion problem.